Lost in the Long Transition : Struggles for Social Justice in Neoliberal Chile. - Alexander, William L., 1963- (Lexington Books, 2009)
Presenting case studies by anthropologists, historians, political scientists, and environmental specialists, Lost in the Long Transition critically examines the impact of neoliberal economic and social policies at the local level in post-dictatorship Chile. Topics include privatization of water rights, tuberculosis and public health crises, the role of labor unions, industrial salmon farming, natural resource conservation, the political ecology of copper, struggles for affordable housing, homelessness and citizenship rights, and gender identity issues in the experiences of returned exiles.